Joint Venture - Mujuranto Sihotang (LEGAL BRIEF, 2019)
Investment becomes an arena for an entrepreneur who has capital and has an entrepreneurial spirit. With a passion for profit, investors do everything they can to obtain abundant profits. One way to develop the company is through collaboration with several parties or companies to run a joint business within a certain period, namely by building a new company or commonly called a Joint Venture. The purpose of this research is to find out a juridical study about the information on joint ventures, and to find examples of cases against illegal actions (PMH) in joint ventures and solutions. Arrangements regarding joint ventures themselves are specifically listed in Law No. 1 of 1967 concerning Foreign Investment (PMA). To find out juridical studies of joint ventures and resolve cases of legal battles against joint ventures with this type of research is a type of normative research. In a joint venture contract governed the distribution of national and foreign shares (capital). Foreign parties can have a maximum capital of 95% and a minimum of 5% domestic capital. From this cooperation will form a new legal entity, which is a combination of foreign legal entities and domestic legal entities. Legal protection against shareholders has been outlined in Law No. 1 of 1967 concerning foreign investment. However, this protection is less clear because it does not clearly provide legal protection for minority majority shareholders or shareholders who have a balanced ownership.